Preliminary study of arthropod herbivores and their natural enemies on raspberries (Rubus idaeus L.) in the Western Cape Province - Potterton, Valerie A.(Valerie Ann) (Stellenbosch : Stellenbosch University, 2012)
Study project (M. Sc.) -- University of Stellenbosch.